Selective Harmonic Elimination of an Eleven Level Inverter Using Whale Optimization Technique - Srikanta Kumar Dash; Byamakesh Nayak; Jiban Ballav Sahu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Reduction of total harmonic distortion in multilevel inverters is a difficult optimization problem that includes nonlinear transcendent equations having more than one local minima.This paper deals with the harmonic elimination of cascaded multilevel inverter with equal D.C. sources using a new optimization technique. The objective of this paper is to find the best combination of switching angles to minimize the lower order harmonics and the total harmonic distortion is reduced. For this purpose, a new optimization techniques i.e. whale optimization technique is considered.This algorithm is applied to an 11-level cascaded H-bridge inverter.Results shows that WOA gives better results and effectively minimizes the THD and lower order harmonics